Matter under extreme conditions experiments at the Linac Coherent Light Source. (22nd April 2016) - Glenzer, S H; Fletcher, L B; Galtier, E; Nagler, B; Alonso-Mori, R; Barbrel, B; Brown, S B; Chapman, D A; Chen, Z; Curry, C B; Fiuza, F; Gamboa, E; et al.
Abstract: The matter in extreme conditions end station at the Linac Coherent Light Source (LCLS) is a new tool enabling accurate pump–probe measurements for studying the physical properties of matter in the high-energy density (HED) physics regime. This instrument combines the world's brightest x-ray source, the LCLS x-ray beam, with high-power lasers consisting of two nanosecond Nd:glass laser beams and one short-pulse Ti:sapphire laser. These lasers produce short-lived states of matter with high pressures, high temperatures or high densities with properties that are important for applications in nuclear fusion research, laboratory astrophysics and the development of intense radiation sources. In the first experiments, we have performed highly accurate x-ray diffraction and x-ray Thomson scattering measurements on shock-compressed matter resolving the transition from compressed solid matter to a co-existence regime and into the warm dense matter state. These complex charged-particle systems are dominated by strong correlations and quantum effects. They exist in planetary interiors and laboratory experiments, e.g., during high-power laser interactions with solids or the compression phase of inertial confinement fusion implosions. Applying record peak brightness x-rays resolves the ionic interactions at atomic (Ångstrom) scale lengths and measure the static structure factor, which is a key quantity for determining equation of state data and important transport coefficients. Simultaneously, spectrally resolved measurements of plasmon features provide dynamic structure factor information that yield temperature and density with unprecedented precision at micron-scale resolution in dynamic compression experiments. These studies have demonstrated our ability to measure fundamental thermodynamic properties that determine the state of matter in the HED physics regime.